Penegakan Hukum Piidana dallam Proses Pemeriiksaan Tiillang Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lallu Liintas dan Angkutan Jallan dii Kota Pekanbaru - Haryono, Dodi; ', Safrudin; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Traffic violations often occur in various places, not just in Pekanbaru, but in nearly all parts of Indonesia, therefore, in the latest Formulate Law No. 22 of 2009 concerning road traffic and transport, law enforcement in the criminal investigation process ticketed under the Law No. 22 of 2009 on Traffic and Road Transportation in the city of Pekanbaru is still not in accordance with the laws and regulations No. 22 of 2009, because there are many traffic violators ticketed in the settlement process is done outside the court or pay on the spot, by bribing the police, the level of pekanbaru city public compliance is very low in traffic, almost every day of the traffic violation, constraints that occur in criminal law enforcement in the investigation process ticketed still lack of awareness, discipline, and lack of socialization of the Act, and the sanctions are mild and the efforts made to overcome these obstacles the traffic police continue to disseminate the law and crack down on speeding ticket fines and sanctions against motorists who violate traffic.Keyword: Criminal Law Enforcement - Ticketed Examination Process - Traffic